Teaching for Critical Consciousness During the Student Debt Crisis - Bruno, Gregory (Radical Teacher, 2020)
These teaching notes describe one educator’s experience facilitating dialogue around student debt and college cost in the first-year writing class. Rooted in the work of Paulo Freire, particular attention is paid to the role of critical pedagogy and meaning-making practices in these complex political and economic contexts.